ФІЛОСОФСЬКО ПЕДАГОІЧНА ПАРАДИГМА СЛОВНИКОВОЇ РОБОТИ ЯК ЗАСОБУ АКТИВІЗАЦІЇ ПІЗНАВАЛЬНОЇ ДІЯЛЬНОСТІ УЧНІВ НА УРОКАХ ЛІТЕРАТУРИ (Педагогіка вищої та середньої школи, 2022)
The article highlights the problem of improviry the teaching process in terms of mistering knowledge of literature, in paticular studying artistic trends and separate texts. The author investistigates theoretical and methodical basis of teaching literature from the point o f view of cognitive activity by means of learning the vocabulary.